PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA.: PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA. - sherly sherly; Dhaniel Syam; Setu Setyawan (Universitas Gajayana Malang, 2019)
Abstract The purpose of this research is to prove empirically the impact of company size decision, profitability, and fixed asset intensity toward tax avoidance. The population that used in this research is manufacture factories that listed in BEI in year of 2015-2017. The sample obtained with purposive sampling method. There are 216 samples of companies that match the sample selection criteria. The analytical method used in this study is multiple linear analysis with the using of SPSS 23 application. According to the outcome of the analysis, the company size and profitability affect tax avoidance, and the intensity of fixed asset has no effect on tax avoidance. Key words: company size, profitability, intensity of fixed asset, tax avoidanc